Analysis of Laboratory Experimental Tests on Mixed Oil Disposal (Bilge) from Ships Based on Marpol Annex I: A Case Study of Port of Tanjung Mas Semarang and Port of Tegal - S. Awel and A. R. Fuad (Nature Environment and Pollution Technology, 2023)
Management of marine pollution is a difficult condition to realize, especially the pollution of mixed oil disposal (bilge) resulting from the operation of ships. The oil component has different characteristics compared to the essence of other substances; namely, oil can float on the surface of the water because it has an extra weight the type/density of the essence. The parameters tested in this research are oil/fat content parameters and their extraction according to National Certification Institution 6989.59:2008. Bilge water samples were taken from five commercial ships that leaned on the port and then carried out pre-treatment and post-treatment tests with the liquid separation process in the Oil Water Separator (OWS) device on the ship and then tested in the laboratory to determine the infrared spectrum in the absorption of oil content emissions in water samples, which may not exceed the standard threshold for port water quality, i.e., 5 mg.L-1. The sampling tests were carried out for the variables temperature, pH, Total Dissolved Solid (TDS), and oil content obtained values were below the threshold for water quality. To find out the relationship between Group I and Group II, linear regression was used showing the Ho result in reject (0.000<0.05), which means there is a significant relationship between Group I and II.